Techno-economic Analysis of a Cascade Biorefinery for Valorizing Agro-industrial Waste: a Case Study of Avocado Hass Seed (persea Americana) from the Amazon Region, Colombia - Sofia Garcia-Maza; Anibal Alviz-Meza; Angel D. Gonzalez-Delgado (Chemical Engineering Transactions)
This study evaluated the feasibility of a cascade biorefinery of Hass avocado seed for producing biocontrol agents, biofilms, and starch in the Amazon region of Colombia. The feasibility was evaluated through simulation in Aspen Plus® and economic analysis. The total investment capital was estimated at USD 1,624,733. The payback period was 1.39 years, the return on investment was 37.58%, and a net present value of 2.62 MMUSD, confirming the financial solidity of the process. In addition, the results also show a depreciated gross profit of USD 860,232.83, a net profit of USD 610,507.12, and a total product cost of 1.61 MMUSD per year. This research opens new perspectives for developing biorefineries in tropical regions, promoting innovation, and green-technologies adoption.